2021
DOI: 10.4049/jimmunol.2100210
|View full text |Cite
|
Sign up to set email alerts
|

Protein Immunization Induces Memory CD4+ T Cells That Lack Th Lineage Commitment

Abstract: Acute viral infection generates lineage-committed Th1 and T follicular helper (Tfh) memory cells that recall their lineage-specific functions following secondary challenge with virus. However, the lineage commitment of effector and memory Th cells in vivo following protein vaccination is poorly understood. In this study, we analyzed effector and memory CD4+ T cell differentiation in mice (Mus musculus) following adjuvanted glycoprotein immunization compared with acute lymphocytic choriomeningitis virus infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
(60 reference statements)
2
1
0
Order By: Relevance
“…The lack of IFN-expressing cells in the GP(1 o ) group was expected, as we previously reported that adjuvanted rGP immunization induces expansion of a CXCR5-IFN-nonpolarized T helper cell population in lieu of highly IFN-expressing Th1 cells as seen following LCMV infection (60). Together, these data show that both adjuvanted rGP immunization and LCMV infection induced I-A b :gp66-77 tetramer+ memory CD4+ Tfh and non-Tfh cells.…”
Section: Generation Of Antigen-specific Memory Tfh Cells In Rgp-immun...supporting
confidence: 81%
See 2 more Smart Citations
“…The lack of IFN-expressing cells in the GP(1 o ) group was expected, as we previously reported that adjuvanted rGP immunization induces expansion of a CXCR5-IFN-nonpolarized T helper cell population in lieu of highly IFN-expressing Th1 cells as seen following LCMV infection (60). Together, these data show that both adjuvanted rGP immunization and LCMV infection induced I-A b :gp66-77 tetramer+ memory CD4+ Tfh and non-Tfh cells.…”
Section: Generation Of Antigen-specific Memory Tfh Cells In Rgp-immun...supporting
confidence: 81%
“…When we analyzed for IFNγ-expressing memory CD4+ T cells in spleen following gp61-80 peptide restimulation and normalized to IFNγ background expression in naïve CD4+ T cells, there was a significantly higher frequency and number of IFNγ-expressing cells in the LCMV(1°) group ( Figs S1C-D ). The lack of IFNγ-expressing cells in the GP(1°) group was expected, as we previously reported that adjuvanted rGP immunization induces expansion of a CXCR5–IFNγ– nonpolarized T helper cell population in lieu of highly IFNγ-expressing Th1 cells as seen following LCMV infection (60). Together, these data show that both adjuvanted rGP immunization and LCMV infection induced I-A b :gp66-77 tetramer+ memory CD4+ Tfh and non-Tfh cells.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation